2016
DOI: 10.3390/ijms17091514
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Metabolomics Revealed the Cytoprotection of Amentoflavone, a Natural Compound, in Lipopolysaccharide-Induced Injury of Human Umbilical Vein Endothelial Cells

Abstract: Amentoflavone is one of the important bioactive flavonoids in the ethylacetate extract of "Cebaiye", which is a blood cooling and hematostatic herb in traditional Chinese medicine. The previous work in our group has demonstrated that the ethylacetate extract of Cebaiye has a notable antagonistic effect on the injury induced by lipopolysaccharide (LPS) to human umbilical vein endothelial cells (HUVECs). The present investigation was designed to assess the effects and possible mechanism of cytoprotection of amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The significant downregulation of citrulline levels and upregulation of proline and glutamate levels in students with CFS under the effect of aerobic exercise intervention indicated that the hydrolysis of arginine to urea and ornithine was restored. Spermine in the spermidine and proline metabolic pathway is produced from putrescine and S-adenosylmethionine catalyzed by various enzymes, providing greater stability and flexibility to DNA molecules, with a cell proliferation-promoting cell function [ 85 ]. Therefore, the ameliorative effect of aerobic exercise on fatigue in students with CFS may be related to the enhanced ability of the body to scavenge free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…The significant downregulation of citrulline levels and upregulation of proline and glutamate levels in students with CFS under the effect of aerobic exercise intervention indicated that the hydrolysis of arginine to urea and ornithine was restored. Spermine in the spermidine and proline metabolic pathway is produced from putrescine and S-adenosylmethionine catalyzed by various enzymes, providing greater stability and flexibility to DNA molecules, with a cell proliferation-promoting cell function [ 85 ]. Therefore, the ameliorative effect of aerobic exercise on fatigue in students with CFS may be related to the enhanced ability of the body to scavenge free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ornithine as a unique downregulated metabolite in group VA was involved in the arginine and proline metabolic pathway, which showed the highest influence value ( Figures 5C, D ). Moreover, ornithine also participated in the regulation of glutathione metabolic pathway ( 43 , 44 ), which may play a role during VA treatment. Therefore, it was suggested that ornithine might be a promising biomarker of VA therapy for MM ( Figures 6A–C ).…”
Section: Discussionmentioning
confidence: 99%
“…These intrinsic metabolism disorders may highly relate to their principal metabolic pathways, and maintain unlimited proliferation and thus are vulnerable to anticancer drugs that impair their vital metabolic pathways. 21 …”
Section: Discussionmentioning
confidence: 99%